2017
DOI: 10.18632/oncotarget.22362
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I induces chemoresistence to docetaxel by inhibiting miR-143 in human prostate cancer

Abstract: Elevated levels of insulin-like growth factor-I (IGF-I) are associated with carcinogenesis and cancer progression. However, the molecular mechanisms by which IGF-I promotes prostate cancer development remain to be elucidated. Docetaxel chemotherapy is an important therapeutic strategy in many types of human cancers including prostate cancer. In this study, we showed that IGF-I rendered PC-3 and DU145 cells more resistant to docetaxel treatment. IGF-I treatment decreased miR-143 expression, but increased the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…Our results are consistent with data on other cancers, where, upon delivery of MIR143 or MIR145 , an inhibition of pancreatic, breast, or colon carcinoma growth in mice models can be achieved 48, 60, 61. Recently, Niu et al 62 . showed that injection of stably MIR143 -transduced PC-3 cells into mice generated smaller xenograft tumors.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with data on other cancers, where, upon delivery of MIR143 or MIR145 , an inhibition of pancreatic, breast, or colon carcinoma growth in mice models can be achieved 48, 60, 61. Recently, Niu et al 62 . showed that injection of stably MIR143 -transduced PC-3 cells into mice generated smaller xenograft tumors.…”
Section: Discussionsupporting
confidence: 92%
“…RIPA lysis and extraction buffer were used to lyse cells on ice for 30 min as previously described (Niu et al, 2017). Samples were separated by SDS-polyacrylamide gel electrophoresis (SDS-PAGE) and transferred to membranes.…”
Section: Immunoblottingmentioning
confidence: 99%
“…They have been recently implicated in the regulation of tumorigenesis by inhibiting major signaling pathways (Pasquinelli, 2012;Xu et al, 2013;Jiang et al, 2018). Some major signaling pathways have been reported to be influenced by different microRNAs in various diseases, including the PI3K/AKT pathway, MAPK/ERK pathway, the mTOR /p70S6K1 pathway, and the TGFβ signaling pathway (Xu et al, 2012;He et al, 2013;Wang et al, 2014;Niu et al, 2017;Jin et al, 2018;Lam et al, 2018). miR-143 has been demonstrated as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs have the ability to post-transcriptionally regulate a wide array of genes, with nearly a third of genes thought to undergo some form of miRNA-mediated regulation (Lu et al, 2005). Depending on the specific miRNA and context, these noncoding RNAs can serve to promote or suppress tumor growth, leading to their dysregulation in many cancers (Ling et al, 2013;Niu et al, 2017;Ge et al, 2018). miR-7 has been found in recent years to serve as a tumor suppressor in several tumor types, but its role in GC has not previously been demonstrated.…”
Section: Discussionmentioning
confidence: 99%